Membangun Keadilan Ekonomi: Alokasi dan Distribusi Pendapatan Negara Menurut Perspektif HUKUM Islam - Ratnasari, Ai Reni; Janwari, Yadi; Hasanuddin, Muhammad; Anggraeni, Desi Cahya; Gofur, Abdul (CV. Strata Persada Academia, 2025)
Income distribution inequality, unequal access to resources, and high poverty levels indicate that the current economic in Indonesia system still faces challenges in achieving social justice. Islamic economic principles emphasize the importance of fair wealth distribution through mechanisms such as zakat and waqf, which serve as social safety nets for underprivileged groups. This study analyzes the allocation and distribution of national income from the perspective of Islamic law, focusing on the implementation of zakat and waqf as key instruments in income redistribution. The research employs a normative-conceptual approach by analyzing Islamic legal sources and academic literature related to state fiscal policies from the perspective of Islamic economics. The findings indicate that optimal management of zakat and waqf can enhance societal welfare and strengthen economic justice. The government plays a crucial role in regulating and integrating Sharia principles into fiscal policies, including centralized zakat management and market regulations that prevent monopolistic practices and economic exploitation. As a recommendation, a professional and transparent zakat and waqf administration system is needed to improve the effectiveness of fund distribution.